DINAMIKA HUKUM PERWALIAN NIKAH DALAM KONTEKS KEMANDIRIAN PEREMPUAN MUSLIM MILENIAL - Azhari, Azhari (Gapenas Publisher, 2024)
The research centered on the tension between traditional marriage guardianship laws, where the guardian holds full authority, and the reality of the independence of millennial Muslim women who have become autonomous and active subjects in making their life choices. This tension creates a gap between formal rules and social practice. This research is designed as library research. In this study, the validity test is focused on credibility through triangulation of sources. The results of the study show that: 1). From Authority to Approval: There has been a paradigm shift in understanding religious texts. The role of the guardian is no longer seen as an absolute authority that must be obeyed, but as a party who gives approval and blessing in a partnership contract. This understanding was born from a reinterpretation that emphasized the principles of voluntariness and equality. 2).. Support system vs. Gatekeeper: In practice, the guardian has two faces. On the one hand, it can be a